Mastering New Information through Facebook and a Discussion Forum: A Comparative Analysis - Nantha Kumar Subramaniam; Maheswari Kandasamy, (Asian Association of Open Universities (AAOU), 2014)
This paper investigated the effect of productive failure (PF) as an instructional strategy in computer-supported collaborative learning (CSCL) groups using Facebook and a discussion forum. PF is an instructional mode design that advocates the delaying of support for the learners during learning — the more they struggle, and even fail, while trying to master new information, the better they are likely to recall and apply that information later. PF has been used successfully in the classroom. However, it is not known whether the use of a PF instructional mode with adult learners in CSCL groups such as Facebook and discussion forums will produce such a positive effect. A discussion forum is an important platform used to deliver teaching and learning via the Web, while the use of social media, especially Facebook, for teaching and learning has gained prominence lately. This paper reports an initial study that compares a ‘productive failure’ instructional design in CSCL groups through Facebook and a discussion forum. Five Facebook and five discussion forum groups participated in the study. Both groups solved ill-structured complex problems in small groups without the provision of any support or scaffolding from their instructors. The findings suggest that the Facebook groups produced a variety of scope for discussion and deliberation for solving the problems and were more successful in sustaining the discussion compared to the discussion forum groups. Facebook groups also had a higher critical thinking ratio than the discussion forum groups. Based on these findings, the implications of a PF instructional design for adult learners are presented. [ABSTRACT BY AUTHORS]